Antibodies to the receptor-binding domain of the SARS-Cov-2 spike protein: association with age, pneumonia, duration of the period after COVID-19 - E. A. Kolosova; O. N. Shaprova; Yu. A. Nikulina; D. V. Shanshin; V. S. Nesmeyanova; Yu. A. Merkuleva; S. V. Belenkaya; A. A. Isaeva; D. N. Shcherbakov; S. A. Elchaninova; M. A. Nikonorova (Журнал инфектологии, 2022)
Despite the rapid accumulation of facts about the humoral immune response in COVID-19, there are still no evidencebased answers to questions about the factors influencing the level and duration of the detection period of antibodies to SARS-CoV-2 in the blood.Objective: To assess the prevalence, clinical and demographic associations of IgG antibodies to RBD of the SARSCoV-2 spike protein at different times after COVID-19.Materials and methods. Residents of the Altai region of Russia, Caucasians aged 20-93 years, who had COVID-19 from May 2020 to February 2021 (n = 314), took part in a onetime observational study. The level of antibodies in the blood was measured by enzyme-linked immunosorbent assay 1-14 months after the onset of the clinical manifestation of COVID-19.Results. Anti-RBD IgG antibodies of the SARS-CoV-2 spike protein were detected in 86.9% of the study participants. The dependence of the antibody titer on the duration of the period after COVID-19 was not revealed. The antibody titer was positively correlated with the complication of COVID-19 pneumonia and the volume of lung tissue lesions. The presence of pneumonia COVID-19 and the volume of lung tissue lesions are positively associated with age. Age positively correlated with antibody titer regardless of the pneumonia COVID-19 in the anamnesis.Conclusion. IgG antibodies to RBD of the SARS-CoV-2 spike protein are present in most of the COVID-19 patients. The titer of these antibodies in adults depends on age, complications of pneumonia COVID-19, and probably persists up to 14 months after the first symptoms of infection appear.